Optimal Power Flow Analysis of a Distributed Generation System. (2015) - Dulău, Lucian-Ioan; Abrudean, Mihail; Bică, Dorin
Abstract: This paper describes the mathematical modeling of the optimal power flow problem. The purpose is to optimize the power flow for a whole day, for a system in which several distributed generators (DGs) have been added. There are two objective functions which are minimized, the generation cost and the total power losses of the system, while satisfying equality and inequality constraints. The optimization is performed for different DGs and load scale factors. The other generators from the system have a 1 scale factor.